2017
DOI: 10.18632/oncotarget.22340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of diametrically polarized tumor-associated macrophages in multiple myeloma

Abstract: Tumor-associated macrophages (TAMs) are correlated with the prognosis of different types of solid tumors and lymphoma, according to many clinical studies. In vitro experiments have demonstrated the roles of these cells in myeloma cell survival, angiogenesis, immunomodulation, drug resistance, and the interaction between malignant myeloma cells and the microenvironment. Here, we investigated the prognostic significance of TAMs in patients with multiple myeloma (MM). We evaluated the polarized functional status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 36 publications
(38 reference statements)
9
48
0
1
Order By: Relevance
“…43,44 High levels of macrophage infiltration, in particular cases with a dominance of macrophages with M2-like phenotypic traits have been reported to be negative prognostic factors for myeloma patient survival. [45][46][47] In line with previous reports, 14 we found that intact IFN-g signaling was necessary for macrophage-mediated tumor rejection. Although we have previously shown that intratumoral delivery of IFN-g may significantly delay tumor outgrowth in a T-cell-independent manner, presumably through direct effects on tumor-associated macrophages, 14 IFN-g in itself is insufficient to induce a tumoricidal phenotype in tumor-associated macrophages ex vivo, 22 suggesting that this cytokine is required, but not sufficient for tumor rejection.…”
Section: Discussionsupporting
confidence: 91%
“…43,44 High levels of macrophage infiltration, in particular cases with a dominance of macrophages with M2-like phenotypic traits have been reported to be negative prognostic factors for myeloma patient survival. [45][46][47] In line with previous reports, 14 we found that intact IFN-g signaling was necessary for macrophage-mediated tumor rejection. Although we have previously shown that intratumoral delivery of IFN-g may significantly delay tumor outgrowth in a T-cell-independent manner, presumably through direct effects on tumor-associated macrophages, 14 IFN-g in itself is insufficient to induce a tumoricidal phenotype in tumor-associated macrophages ex vivo, 22 suggesting that this cytokine is required, but not sufficient for tumor rejection.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, polarization of TAMs toward the M2 phenotype as reflected by lower M1/M2 ratio was an independent predictor for poor response to CT or RT and shorter survival in LACC (39). This was supported by other studies involving different cancer types such as ovarian cancer (40), pediatric classical Hodgkin lymphoma (cHL) (41), and multiple myeloma (42).…”
Section: M1/m2 Ratio As the More Amenable Means Of Cancer Prognosticasupporting
confidence: 62%
“…2B and Table S3). Clustering the plasma cells of MGUS04 shows that the malignant cells (in cluster 4) are characterized by a transcriptional signature overexpressing a known MM driver (CCND1), along with DPEP3 (p<1x10 -50 ), a dipeptidase involved in arachidonic acid metabolism, previously associated with triple negative breast cancer, but not with MM (Table S2) 41 . These malignant PC originate from a single BCR clonotype.…”
Section: Characterizing Rare Cancer Cells In Asymptomatic Patients Anmentioning
confidence: 99%